The Relationship Between Knowledge About Smoking Hazards and Self-Efficacy for Smoking Cessation Among Vocational High School Students - Zidan, Muhammad; Puspita, Tantri; Sugih Permana, Gin Gin (CV. Literasi Publikasi Indonesia, 2025)
This study aimed to analyze the relationship between knowledge about the dangers of smoking and self-efficacy for smoking cessation among adolescents. A descriptive correlational design with a cross-sectional approach was used, involving 203 smoking students at SMKN 4 Garut, Indonesia. Validated and reliable questionnaires were used to measure knowledge and self-efficacy. Results showed that most respondents had good knowledge (61.1%) and high self-efficacy (66%). Spearman’s Rank correlation test revealed a strong positive relationship between knowledge and self-efficacy (r = 0.737, p = 0.001). The study concludes that higher knowledge about smoking hazards is associated with higher self-efficacy for quitting smoking among vocational high school students.